Pharmacokinetics of Cefamandole nafate in a new dosage form - Torres, William Deloso 1943-
Three suppository bases made from mixtures of polyethylene glycols and polyethylene glycol ether were selected for further evaluation when combined with cefamandole nafate powder. Cefamandole nafate (Mandol R, Lilly) is a new parenteral cephalosporin with extended gram-negative in vitro activity. It is active against gram-negative bacilli, gram-positive cocci and some anaerobic organisms. The selected bases were evaluated in vitro as to hardness, friability, uniformity, melting point, stability at selected storage temperatures, and dissolution properties at physiological conditions [37(degrees C) and pH 6.2]. In vitro and in vivo tests were conducted using the vaginal suppositories containing cefamandole nafate. Parous rabbits were used in this experiment. High performance liquid chromatography (HPLC) was used to analyze amounts of cefamandole in dissolution and plasma samples. The pharmacokinetic parameters were determined from the plasma concentrations of cefamandole versus time for each formulation in each rabbit based on a 3x3 Latin square design.
Parameters such as areas under the concentration versus time curves (AUCs), time spans that the minimum inhibitory concentrations (MICs) against gram-negative and gram-positive microorganisms were maintained, and lag times were compared and evaluated for all three formulations. Analysis of variance (ANOVA) was used to determine sources of variation in each parameter and to predict if the variations were significant or not. The AUTOAN program was used to analyze the data generated by the three vaginal suppository formulations. Results indicated that the data are best described by a one-compartment open model with a lag time. The bioavailability of cefamandole from the vaginal suppository formulations was also compared with that of an equivalent intravenous dose. Results of in vitro studies indicated good hardness and friability, uniformity, dissolution properties, and stability for all three formulations. The in vivo results indicated comparable bioavailability of cefamandole from both the vaginal suppository and the intravenous dose. This work demonstrated that cefamandole could be absorbed from a vaginal suppository form. This could provide an alternate route of administering cefamandole and other cephalosporins that are currently available only in parenteral forms.
Available to the general public.
Thesis (Doctor of Philosophy in Pharmacy)--University of Mississippi, May 1980.
Keywords: Pharmacokinetics; Cephalosporins; Drugs -- Dosage forms; Dosage Forms